Analisis Ujicoba Terbatas pada Bahan Ajar Fisika dengan Konten Nilai Kecerdasan Spiritual Materi Gerak Dua Dimensi dan Hukum Newton untuk Siswa Kelas X SMA - Silvi Atika Sari; Zulhendri Kamus; Asrizal Asrizal (PILLAR OF PHYSICS EDUCATION, 2018)
Physics learning in 2013 curriculum demands students to apply the spiritual attitudes of competence. For this reason, physics teaching material should support the achievement of core competence especially the spiritual competence. But the real condition physics teaching material in schools didn’t include the spiritual intelligence content yet. Solution of this problem is to develop of physics teaching material that contain content value of spiritual intelligence. The purpose of this research is to produce physics teaching material with spiritual intelligence content on two dimensional motion and Newton’s laws of motion that has both practice and effective criteria. This research can be included into research and development (R&D) type. The development model in research was Sugiyono’s development model. This development model consists of ten stages, but in this research only use six stages, namely potential and problem, data collection, product design, design validation, design revision, and poduct testing. The object of research was physics teaching material with spiritual intelligence content. The instruments that used in research were practicality assessment sheet, the learning result sheet, and spiritual attitude assessment sheet. The data analysis technique were descriptive statistical analysis and comparative test of one group of sample. Based on data analysis can be presented two results of this reseacrh. First, the use physics teaching material with spiritual intelligence content is practice according to physics teachers and learners with average value were 85.70 and 82.49 respectively. Second, the use physics teaching material with spiritual intelligence content is effective in scientific approach to improve the knowledge and spiritual attitudes competences of learners.